Multilayer MXene framework for construction of hierarchical structure composites for high performance metal ion batteries - Guo, Peng; Singer, Lennart; Zhao, Zhiyong; Hinz, Brian; Kędzierski, Tomasz; König, Tobias; Mijowska, Ewa; Zharnikov, Michael; Comba, Peter; Klingeler, Rüdiger (Electrochimica acta, 2025)
MXenes have become promising candidates for metal ion battery anodes. However, the achievable capacities of bare MXene-based electrodes are still limited. A promising strategy to overcome this issue and still exploit the unique properties of MXenes is to design composites of the MXenes and high-capacity conversion or alloy-type anode materials. Despite the growing interest in these kinds of MXene-based composites, the utility of multilayer MXene with its unique accordion-like structure is, even though it promises many advantages, such as a large surface area and a unique open structure, rarely reported. Here, we report on the preparation of hierarchical MoO2/C/V2C composites by an electrostatic interaction-assisted hydrothermal method and a post-annealing process. Our composites exhibit a unique hierarchical structure, where the MoO2 nanoparticles are confined and uniformly distributed in the open V2C/C layered framework. This architecture enables fast-ion and electron transfers and nicely accommodates the volume changes of MoO2 during cycling. Therefore, when used for lithium-ion batteries, the composites exhibit outstanding long-term cycling performance at high current densities of 1 and 2 A g-1. Our results demonstrate the benefits of using an accordion-like MXene host-framework for the composite formation and highlight the potential of such composites for high performance metal ion batteries.
Gesehen am 21.10.2025